COMPATIVE EFFECTS OF INDUCED WATER STRESS ON NUTRIENT UPTAKE AND WATER-SOLUBLE CARBOHYDRTAES ACCUMULATION IN SUGAR BEET AND WHEAT - ABAYOMI, Y. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Two experiments were conducted to investigate the comparative effects of water stress induced at different growth stages on Nitrogen (N), phosphorus (P), potassium (K) and sodium (Na) uptake and water-soluble carbohydrate (WSC) accumulation in two contrasting crop species. The first trial investigated the effect of water stress at four growth stages in one variety each of wheat (Triticum aestivum (L), var Webley) and sugar beet (beta vulgaris (L) var Gala), while in the second trial water stress was induced at two growth stages of both crop species in the second trial. Water stress at any of the growth stages significantly reduced N, P, K and Na uptake in wheat, while it had no appreciable effects on nutrients uptake in sugar beet. However, water stress at any of the growth stages significantly increased water-soluble carbohydrate accumulation I wheat leaves, while the parameter did not show consistent response to water stress (late and very late) resulted in increased WSC in the species. This study revealed significant relationship between reduced nutrient uptake and decreased grain yield in wheat, while in sugar beet, there was no evidence to suggest that any response to water stress was related to rduce nutrient uptake. These results suggest that reduced nutrient uptake due to water stress can play significant role in yield reduction in wheat but not in sugar beet.